Jual Beli Akun Game Online Dalam Perspektif Maqashid Asy- Syariah - Dawwir Rif'ah (Jurnal Ilmiah Ekonomi Islam, 2022)
Abstract practice of online gaming accounts by teenagers to adults has become one of many forms of commerce in any system of income at any time or place with no age restrictions as stipulated in civil law. In addition to being an Internet use for the use of these online games is much appreciated by young people even children as a kind of personal entertainment and the gaining of advantages through a race known as the tournament. And so a review of what is needed in the use of these online gaming accounts is a consideration of the benefits and the madharat that over time are also likely to lead to addiction. The akirate online gaming accounts are valid under the terms of the fiqih muamamallah, but on the other hand must be balanced by the clean principles that naturally refer to maqashid asy-sharia as part of the basic human needs of dharuriyyat, hajiyyat, and tahsiniyyat. The purpose of the article was to analyze by using the empirical judical method and also by the data of related theories. The study is the combination of theoretical and field studies proved by interviews of both sellers and buyers and the use of theories based on the opinions of scholars who refer to the law.